Manuel Reyes Mate: aportes de su pensamiento a una comprensión ética de las víctimas en el contexto colombiano (2014)
This article is the product of a reflection and analysis of Manuel Reyes Mate’s thought which seeks to provide elements of critical reflection regarding the debate on ethics of the victims. In the first part, the article approaches the relevance or social, philosophical and institutional importance of this topic. The second part allows a reflection on the necessity to think ourselves from other possibility; to rethink the consequences that emerged from Auschwitz for all humanity and to identify who are the victims, permitting us to comprehend and situate better the thought of Reyes Mate.In a third moment, the article investigates over the central elements for a new ethical conception from the victims. It also focuses on how memory can be converted into political mobilization to promote and claim the dignity of the excluded, marginalized and victims of violence. Equally, it offers some elements of reflections to think history and the future of humanity from a new ethical conception where anamnesis justice, memory, compassion and solidarity confront the current thesis of justice and historical positivism and where the victims are turned into new pillars to rebuilt and rethink the future of society. In the end, the article proposes a brief reflection that aims at contextualizing who are the victims and their current situation and the incidence of the diverse experiences of memory recovery in the country, which permits us to highlight the challenges and requirements that can be expected by the Colombian society, according to the contributions of Reyes Mate.